EVALUATION OF A METHOD FOR THE DESTRUCTION OF EXPIRED SODIUM METAL ON A LABORATORY SCALE - Jiménez-Prieto, Yamell; Esperanza-Pérez, Guillermo; Ramírez-González, Surey; Martin-Santin, Javier; Ribalta-Quesada, Juan A. (Revista Cubana de Química, 2024)
In the present work was to asses, on a laboratory scale, a method for the destruction of expired metallic sodium under safe conditions. For this, its reaction with ethanol was studied, which occurs in two stages. The variation of the temperature of the reaction system as a function of the sodium dosing rate, the mass ratio of technical ethanol/sodium depending on the weight percent of the ethanol used, the need for water in the second stage, and the stirring speed were experimentally investigated. From these tests, the parameters were obtained, to safely carry out the destruction of this metal. Finally, an elemental characterization of the waste formed was carried out, proposing several alternatives for its management, highlighting that more than 98 % of the ethanol used in the first stage is recovered by distillation, guaranteeing its reuse